BERPIKIR KREATIF MATEMATIS SISWA KELAS VIII DALAM MEMECAHKAN SOAL HOTS BERDASARKAN PERBEDAAN JENIS KELAMIN - Sabbriani, Nisvi; Sujarwo, Imam (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Every student's mathematical creative thinking can change at any time or have a dynamic nature (Astra et al., 2022). These changes can be caused by the level of difficulty of learning materials and the students themselves. The research data was taken through the results of giving HOTS (High Order Thinking Skill) questions about flat shapes to class VIII MTs Negeri 1 Malang City. The questions are validated before being given to students, in order to measure the level of creative thinking in students. This research is a qualitative descriptive study that uses time triangulation in collecting data. By testing 4 (four) Guilford creativity indicators consisting of originality, elaboration or detail, fluency and flexibility in the research subject. The research subjects who were given HOTS questions and interviews were 2 male students and 2 female students. Test data were collected twice at different times and interviewed twice after giving HOTS questions. The results of the study can be concluded that, men and women fulfill 4 (four) Guilford creativity indicators. However, male students have a prominent indicator of flexibility and female students naturally have an indicator of originality. This study shows that Guilford's creativity which links cognitive and creative thinking can be tested on students' thinking abilities. There is an influence of gender on the indicators of flexibility and originality. This is because there are patterns of interaction, then the ability to explore and describe each of the different male and female students.